2006
DOI: 10.1007/s00125-006-0422-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of dietary patterns, meat intake and the risk of gestational diabetes mellitus

Abstract: Aims/hypothesis The aim of this study was to prospectively examine whether dietary patterns are related to risk of gestational diabetes mellitus (GDM). Methods This prospective cohort study included 13,110 women who were free of cardiovascular disease, cancer, type 2 diabetes and history of GDM. Subjects completed a validated semi-quantitative food frequency questionnaire in 1991, and reported at least one singleton pregnancy between 1992 and 1998 in the Nurses_ Health Study II. Two major dietary patterns (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
251
9
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(291 citation statements)
references
References 52 publications
24
251
9
7
Order By: Relevance
“…Women in the Western Type class had the highest intakes of red and processed meat, butter and lard and highfat dairy products, and might thus have been exposed to a higher intake of saturated fats and trans fatty acids. Zhang et al (2006) found an increased risk of gestational diabetes in women following a Western diet in contrast to women following a Prudent diet, and the difference was suggested to be because of the higher intake of red and processed meat, leading to a higher intake of saturated fatty acid and cholesterol. Trans-fatty acids were found to be negatively correlated with birth weight (Koletzko, 1992;Elias and Innis 2001;Larque et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Women in the Western Type class had the highest intakes of red and processed meat, butter and lard and highfat dairy products, and might thus have been exposed to a higher intake of saturated fats and trans fatty acids. Zhang et al (2006) found an increased risk of gestational diabetes in women following a Western diet in contrast to women following a Prudent diet, and the difference was suggested to be because of the higher intake of red and processed meat, leading to a higher intake of saturated fatty acid and cholesterol. Trans-fatty acids were found to be negatively correlated with birth weight (Koletzko, 1992;Elias and Innis 2001;Larque et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Higher consumption before pregnancy of total red meat and processed red meat (beef, lamb, pork, hamburger, bacon, beef hot dogs and sausages, salami and bologna) were significantly associated with increased risk of GDM in the Nurses' Health Study II (25,26). For each increase of 1 serving/day of total red meat or processed red meat, GDM risk increased by 66% (95% CI 1.36%, 2.02%) and 47% (95% CI 0.98%, 2.20%), respectively (25).…”
Section: Red and Processed Meatmentioning
confidence: 99%
“…Two studies examined associations between dietary patterns and GDM (26)(27)(28)(29). Findings from the Nurses' Health Study II provided evidence on prepregnancy dietary patterns and development of GDM (26-28).…”
Section: Associations Between Dietary Patterns and Gdmmentioning
confidence: 99%
“…Over the years, a number of pre-pregnancy dietary factors have been found to be significantly associated with GDM risk (Table 1). Among these, potentially harmful factors include sugar-sweetened beverages [15], heme iron intake [16], fried foods [17], animal fat [18] and animal protein [19], a diet low in carbohydrate but high in animal fat and protein [20], as well as an overall western dietary pattern as characterised by a high intake of red meat and processed meat, refined grain products, sweets, French fries and pizza [21]. A recent study using the NHS-II data reported that greater potato consumption was related to an increased GDM risk [22].…”
mentioning
confidence: 99%
“…A recent study using the NHS-II data reported that greater potato consumption was related to an increased GDM risk [22]. Potential beneficial factors include a prudent diet, characterised by a high intake of fruit, green leafy vegetables, poultry and fish [21], a Mediterranean diet [23], as well as nut [19] and fibre consumption [24]. Findings from the investigation of joint effects of diet and physical activity, cigarette smoking and BMI indicated that more than 45% of GDM cases might have been prevented if women adopted an overall healthy diet and lifestyle and maintained a healthy body weight before pregnancy [25].…”
mentioning
confidence: 99%